Risk factors and molecular mechanisms associated with trimethoprim–sulfamethoxazole resistance in Stenotrophomonas maltophilia in Mexico - Herrera Heredia, Sandra Abril; Pezina Cantú, César Octaviano; Garza González, Elvira; Bocanegra Ibarias, Paola; Mendoza Olazarán, Soraya Sarahí; Morfín Otero, Rayo; Camacho Ortiz, Adrián; Villarreal Treviño, Licet; Rodríguez Noriega, Eduardo; Palau Davila, Laura; Maldonado Garza, Héctor Jesús; Flores Treviño, Samantha Maribel (2017)
Abstract Purpose. Stenotrophomonas maltophilia is a multidrug-resistant opportunistic pathogen causing an increasing number of nosocomial infections. Our aim was to evaluate the risk factors and mechanisms associated with trimethoprim– sulfamethoxazole (SXT) resistance in S. maltophilia infections in Mexico. Methodology. Clinical isolates and patients’ demographic and clinical data were collected from February 2007 to August 2015 in two tertiary-care hospitals in Mexico. Antimicrobial susceptibility and analysis of sul and SmeABC and SmeDEF efflux pump overexpression were performed in all isolates. Results/Key findings. In the 9-year period, 196 patients infected with S. maltophilia were identified. Most patients were male, and the mean age was 46.2years. The mean Charlson score was 1.42, and the most frequent comorbidities were arterial hypertension (26.7%), type 2 diabetes (21.2%) and cerebral infarction (11.6%). High drug resistance to meropenem (93.4%), gentamicin (55.1%), ceftazidime (52.3%), cefotaxime (51.5%), amikacin (42.3%) and cefepime (32.1%), and lower resistance to ciprofloxacin (26.0%), SXT (25.0%), chloramphenicol (14.3%) and levofloxacin (2.6%) were detected. SXT resistance was not associated with the sul genes. SmeABC overexpression was associated with gentamicin (P=0.001) and levofloxacin resistance (P=0.041), whereas SmeDEF overexpression was associated with ceftazidime resistance (P=0.003). Prolonged hospitalization (15days) was an independent risk factor for SXT-resistant S. maltophilia infections (OR=3.05; 95%CI=1.12– 8.86; P=0.029). Conclusion. Given the high SXT resistance rate, SXT is not an effective first-line therapy for our patients; instead, levofloxacin could be used as an appropriate therapeutic option against S. maltophilia infections.